Где валяются поцелуи. Париж - Валиуллин Ринат Рифович (Антология любви, 2017)
Экземпляры: аб. (2018) / Инвентарный номер: 54624 / Цена: / Сис.шифр: 84(2Рос-Рус)6-4 / Авт.знак: В 15 / ББК: 84(2Рос-Рус)6-4